MEASURES TO REVITALIZE INDUSTRIAL TOURISM IN THE NAGOYA AND CHUKYO AREAS OF JAPAN USING STRUCTURAL EQUATION MODELING (Proceedings of the International Conference on Hospitality and Tourism Management, 2023)
During the COVID-19 pandemic, the number of tourists dropped dramatically in most tourist destinations. Industrial tourism can be regarded as a powerful form of community-based tourism in a post-COVID-19 world. This study proposes measures to revitalize industrial tourism in Japan through a case study Nagoya and Chukyo. It analyzes questionnaire survey results from users of industrial tourism facilities using structural equation modeling. Four hundred users of six industrial tourism facilities were surveyed. First, an exploratory factor analysis on the results of the questionnaire surveys was conducted. Then, three factors—"Smooth facility tour", "Dynamism and novelty of the exhibition", and "Purchase of products and services encountered"—were extracted and analyzed using structural equation modeling. The following results were obtained; the latent variables "Smooth facility tour (pass coefficient of standardized solution: 0.600)" and"Purchase of products and services encountered (0.237)" had a positive effect on the observation variable "Satisfaction with the facility". Furthermore, "Dynamism and novelty of the exhibition (-0.332)" had a negative effect on "Satisfaction with the facility". Therefore, the results suggest that new attractions should be added for users who seek dynamic and novel industrial exhibitions in Nagoya and Chukyo. Specific examples include more immersive exhibitions, provision of experience-based programs, and proposals for model courses that include other facilities.
Keywords: industrial tourism; exploratory factor analysis; structural equation modeling; Nagoya; Chukyo